UNUSUAL MASSIVE RECRUITMENT OF THE REEF FISH CTENOCHAETES STRIGOSUS (BENNET) (PERCIFORMES: ACANTHURIDAE) TO THE MINICOY ATOLL AND ITS SIGNIFICANCE - Pillai, C S Gopinatha; Mohan, Madan; Kunhikoya, K K (Indian Journal of Fisheries, 2011)
A sudden influx, and subsequent settlement, of C. strigosus in enormous numbers in the lagoon and on reef flats of Minicoy island, where, but for a couple of specimens dealt with by Jones and Kumaran (1980, this species was almost unknown, is reported. The fish, ranging in length from 50 to 82 mm, which had been obviously leading thus far a pelagic life, were in stages past postlarval, and were already in the process of metamorphosing into adult, with gonads in stages up to Stage III maturity.